Photodegradation of Methylene Blue Dye Using TiO2/Zeolite with the Addition of Nitrate Ions (NO3-) - Erwanto, Erwanto (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the characterization of TiO₂/zeolite composites and determine the amount of TiO₂/zeolite, NO₃⁻ ion concentration, and optimum irradiation time for the photodegradation process of methylene blue in solution. Methodology: This study used X-Ray Diffraction (XRD-6000 Shimadzu), UV-Vis spectrophotometer, UV lamp (Sankyo, 10 W, 352 nm), Teflon type hydrothermal reactor, and photocatalyst reactor (40×40×40 cm). The methods include zeolite activation, TiO₂ dispersion, hydrothermal synthesis, photodegradation test, and data regression analysis. Main Findings: The TiO₂/zeolite composite showed characteristic peaks at 2θ = 25.2737°, 37.6855°, and 48.0278° without any change in the crystal structure. The maximum degradation effectiveness of 29.94% was obtained by adding 75 mg of the composite. The optimum NO₃⁻ concentration was 0.5 M with an irradiation time of 100 minutes resulting in an effectiveness of 30.81%. NO₃⁻ has a dual role in the degradation process. Novelty/Originality of this study: This study developed a photodegradation system with a combination of TiO₂/zeolite composite and nitrate ions. The novelty lies in the simultaneous analysis of the effects of catalyst amount, NO₃⁻ concentration, and irradiation time, as well as revealing the dual role of NO₃⁻ in enhancing and inhibiting degradation.